Detection of clade 2 equine influenza virus in an adult horse recently imported to the USA. (19th March 2014) - Pusterla, N.; Estell, K.; Mapes, S.; Wademan, C.
Summary A 4‐year‐old Warmblood mare presented to the William R. Pritchard Veterinary Medical Teaching Hospital, School of Veterinary Medicine, University of California at Davis with bilateral mucoid nasal discharge and pyrexia. The mare had recently been imported from Germany, arriving at a quarantine holding facility 72 h prior to presentation. Based on clinical presentation and culture results of tracheal fluid, the mare was diagnosed with bacterial bronchopneumonia secondary to equine influenza. The equine influenza virus (EIV) identified in the imported mare displayed 99.1% nucleotide homology of the HA1 gene to the prototype Florida sublineage clade 2 isolate A/equine/Richmond/1/2007 (H3N8). This case illustrates the risk of introducing a clade 2 EIV in North America.